2017
DOI: 10.1039/c7ob02147j
|View full text |Cite
|
Sign up to set email alerts
|

Pseudouridine modifications influence binding of aminoglycosides to helix 69 of bacterial ribosomes

Abstract: Development of antibiotics that target new regions of functionality is a possible way to overcome antibiotic resistance. In this study, the interactions of aminoglycoside antibiotics with helix 69 of the E. coli 23S rRNA in the context of complete 70S ribosomes or the isolated 50S subunit were investigated by using chemical probing and footprinting analysis. Helix 69 is a dynamic RNA motif that plays major roles in bacterial ribosome activity. Neomycin, paromomycin, and gentamicin interact with the stem region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Gentamicin (GM) is an aminoglycoside molecule primarily used as a gram-negative antimicrobial drug due to its ability to bind and cleave the 30S subunit of the bacterial ribosome [12]. Previous studies revealed a nephrotoxic action for high doses of GM with particular focus on both apoptosis [13] and necrosis [14] of tubular epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Gentamicin (GM) is an aminoglycoside molecule primarily used as a gram-negative antimicrobial drug due to its ability to bind and cleave the 30S subunit of the bacterial ribosome [12]. Previous studies revealed a nephrotoxic action for high doses of GM with particular focus on both apoptosis [13] and necrosis [14] of tubular epithelial cells.…”
Section: Introductionmentioning
confidence: 99%